Vitamin C intake potentially lowers total cholesterol to improve endothelial function in diabetic patients at increased risk of cardiovascular disease: A systematic review of randomized controlled trials - Dludla, Phiwayinkosi V.; Nkambule, Bongani B.; Nyambuya, Tawanda M.; Ziqubu, Khanyisani; Mabhida, Sihle E.; Mxinwa, Vuyolwethu; Mokgalaboni, Kabelo; Ndevahoma, Fransina; Hanser, Sidney; Mazibuko-Mbeje, Sithandiwe E.; Basson, Albertus K.; Sabbatinelli, Jacopo; et al. (Frontiers in Nutrition, 2022)
Background: Vitamin C is one of the most consumed dietary compounds and contains abundant antioxidant properties that could be essential in improving metabolic function. Thus, the current systematic review analyzed evidence on the beneficial effects of vitamin C intake on cardiovascular disease (CVD)-related outcomes in patients with diabetes or metabolic syndrome. Methods: To identify relevant randomized control trials (RCTs), a systematic search was run using prominent search engines like PubMed and Google Scholar, from beginning up to March 2022. The modified Black and Downs checklist was used to assess the quality of evidence. Results: Findings summarized in the current review favor the beneficial effects of vitamin C intake on improving basic metabolic parameters and lowering total cholesterol levels to reduce CVD-risk in subjects with type 2 diabetes or related metabolic diseases. Moreover, vitamin C intake could also reduce the predominant markers of inflammation and oxidative stress like C-reactive protein, interleukin-6 and malondialdehyde. Importantly, these positive outcomes were consistent with improved endothelial function or increased blood flow in these subjects. Predominantly effective doses were 1000 mg/daily for 4 weeks up to 12 months. The included RCTs presented with the high quality of evidence. Conclusion: Clinical evidence on the beneficial effects of vitamin C intake or its impact on improving prominent markers of inflammation and oxidative stress in patients with diabetes is still limited. Thus, more RCTs are required to solidify these findings, which is essential to better manage diabetic patients at increased risk of developing CVD.